2008
DOI: 10.1007/s00128-008-9552-0
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated Biphenyls Residues in the Soil in Linfen, China

Abstract: A total of 10 surface soil samples covering the whole territory of Linfen city were collected for analysis the 144 polychlorinated biphenyls (PCBs). The total PCBs concentration ranged from 0.2 to 3.4 ng g -1 in urban soil and 0.5 to 14.8 ng g -1 in industrial plant soil. Furthermore, increasing PCBs contamination was observed in northeast Linfen because of the distribution of industrial plants. Principal component analysis (PCA) revealed that the major source of PCBs in Linfen may be potentially associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
1
0
0
Order By: Relevance
“…The levels of PBCs contamination in the soils studied were much lower than the recommended limits of 25 mg/kg and 33 mg/kg set by the Canadian Soil guide [37], and the US EPA [38], respectively. The levels were comparable to levels detected in soils in Linfen city, China [39], lower than those found in soils elsewhere in Bahrain [40], Moscow region [41], Switzerland [42], Belarus [43], New York [44], Shanghai [45], but higher than those found in Poland [46].…”
Section: Pcb Levels Distribution and Congener Profilesupporting
confidence: 51%
“…The levels of PBCs contamination in the soils studied were much lower than the recommended limits of 25 mg/kg and 33 mg/kg set by the Canadian Soil guide [37], and the US EPA [38], respectively. The levels were comparable to levels detected in soils in Linfen city, China [39], lower than those found in soils elsewhere in Bahrain [40], Moscow region [41], Switzerland [42], Belarus [43], New York [44], Shanghai [45], but higher than those found in Poland [46].…”
Section: Pcb Levels Distribution and Congener Profilesupporting
confidence: 51%
“…The concentration, source, and congener pattern of PCBs in soils have been studied by many scientists all over the world. In China, PCB concentrations in soils of Dalian, Taiyuan, Linfen, Harbin, Hong Kong and so on have been reported in recent years (Zhang et al, 2007;Fu et al, 2008a;Wang et al, 2008;Fu et al, 2009;Ma et al, 2009). However, most of these studies focused on the concentration of PCBs in urban soils, only a few research reported the PCB levels in rural soils (Chen et al, 2008;Shen et al, 2009;Wang et al, 2009;Wu et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%